Retraditionalizing the Quest: A Histori-cultural Case for Contemporary African Developmental Thought Pattern - Balogun, Noah Opeyemi; Oyeniyi, Toluwalope; Ajepe, Ife; Ademowo, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2022)
Critical developmental thinking started as a speculative debate of difference(s) and otherness, metamorphosing through the obstacles of the ideologies of ‘primitive’ mentality, ‘barbaric’ cultures, and ‘uncivilized’ civilizations to its current state. However, it should be stressed that in the process of giving form to the practice of developmental thinking in Africa, philosophers, and cultural studies scholars, especially, have frequently engaged in contentious debates and defensive discourses around the place and pivotal role of culture in development (most especially the role of ethnophilosophic materials). Many perceived this style of thinking as a way of still clinging to the inferior phase of developmental project, instead of ‘moving on’ to modernity with its alluring offers. Sticking with ‘tradition’ or the ‘ethnophilosophic materials’ and all related sorts, such as norms, values, indigenous languages, etc., are therefore pronounced as harmful to development. This work is a departure from the foregoing submission that considers ‘ethnophilosophic’ materials as harmful; our focus is on the place of histori- cultural ingredients in the pursuit of ‘development from below and with people’. This, we submitted, should be of interest to scholars that genuinely seek to rejig African developmental thought pattern, which should be a blend of historical lessons and the much needed culturalchanges.